Optimum currency area and business cycle synchronization across U.S. States - Conraria, Luís Aguiar (2015)
We use wavelet analysis to investigate to what extent individual U.S. states' business cycles are synchronized. The results show that the U.S. states are remarkably well synchronized compared to the previous findings w.r.t. the Euro Area. There is also a strong and significant correlation between business cycle dissimilitudes and the distance between each pair of states, consistent to gravity type mechanisms where distance affects trade. Trade, in turn, increases business cycle synchronization. Finally we show that a higher degree of industry specialization is associated with a higher dissimilitude of the state cycle with the aggregate economy